2023
DOI: 10.1155/2023/5723730
|View full text |Cite
|
Sign up to set email alerts
|

Study of Friction and Wear Behavior of Graphene-Reinforced AA7075 Nanocomposites by Machine Learning

Abstract: In this research, the friction and wear of AA7075 nanocomposites reinforced with graphene and graphite were studied. Graphene’s inclusion dramatically enhanced the material’s mechanical characteristics, friction, and wear resistance. AA7075 is strengthened with less graphene, and AA7075, reinforced with more graphite, exhibits similar wear and friction behavior. Wear rate and coefficient of friction predictions for AA7075-graphene nanocomposites were made using five machine learning (ML) regression models. ML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Te authors [26] found that as the ZrO 2 content of the composites with an Al matrix increased, the porosity of the composites also increased. Te reports show less than 1.5% overall porosity [27]. Te density fndings of this investigation are found to be compatible with the literature.…”
Section: Experimental Densitysupporting
confidence: 90%
“…Te authors [26] found that as the ZrO 2 content of the composites with an Al matrix increased, the porosity of the composites also increased. Te reports show less than 1.5% overall porosity [27]. Te density fndings of this investigation are found to be compatible with the literature.…”
Section: Experimental Densitysupporting
confidence: 90%
“…Nosonovsky et al [21] explored a topological data analysis and various ML algorithms, applying them to various aspects of friction data analysis and friction instability. Prasanth et al [27] predicted the COF of AA7075-graphene nanocomposites using five ML regression models. Kolev et al [28] investigated the tribological behavior of porous AlSi10Mg-SiC composites and used three different ML models to predict the COF of the composite materials, evaluating their performance on validation and test sets using R 2 , MSE, RMSE, and MAE metrics.…”
Section: Introductionmentioning
confidence: 99%